2021
DOI: 10.1080/17405629.2021.1948398
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Well-being during the COVID-19 pandemic: Relationships with attitudes, family structure, and mothers’ Well-being

Abstract: COVID-19 triggered social restrictions worldwide including the shutdown of schools. Whereas research has documented the negative effects on parents' well-being, less is known about children's well-being during the pandemic. We investigated the well-being, emotions, and COVID-19-related attitudes of 87 Norwegian elementary children (42 boys, 45 girls; M age = 9.66 years, SD = 1.77) and their mothers (M age = 39.69 years; SD = 5.79) in June 2020. Children reported reduced well-being relative to European norms. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
3
19
0
3
Order By: Relevance
“…The present study makes an important contribution not only to existing literature on the antecedents and consequences of children's school engagement and well-being under normal circumstances (Fredricks et al, 2004;Upadyaya and Salmela-Aro, 2013), but also to the emerging literature that focuses on the negative consequences of the COVID-19 pandemic on children and parents (Hoffman and Miller, 2020;Spinelli et al, 2020;Martiny et al, 2021). We extend previous work on the effects of lockdowns and school closures on children by examining features of a previously unexplored context: classrooms altered by COVID-related restrictions.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The present study makes an important contribution not only to existing literature on the antecedents and consequences of children's school engagement and well-being under normal circumstances (Fredricks et al, 2004;Upadyaya and Salmela-Aro, 2013), but also to the emerging literature that focuses on the negative consequences of the COVID-19 pandemic on children and parents (Hoffman and Miller, 2020;Spinelli et al, 2020;Martiny et al, 2021). We extend previous work on the effects of lockdowns and school closures on children by examining features of a previously unexplored context: classrooms altered by COVID-related restrictions.…”
Section: Discussionmentioning
confidence: 78%
“…A study from Italy showed that parents' stress during the crisis had a negative impact on children's behavioral and emotional problems (Spinelli et al, 2020). Even in Norway, which experienced a relatively low number of cases and deaths in the first wave of the COVID-19 pandemic in spring 2020, children reported significant costs in well-being when schools were closed during the lockdown (Martiny et al, 2021). Researchers have argued that school closures played a significant role in this decrease in well-being (Hoffman and Miller, 2020), but the impact of the structural changes made to schools to align with COVID-19 restrictions upon reopening have not yet been examined.…”
Section: Children's Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…In Study 2, we recruited elementary school children who were between 6 and 13 years old. The second study was part of a project that investigated the effects of COVID-19 on parents' and children's well-being (Martiny et al, 2021;Thorsteinsen et al, 2021) and also investigated the development of gender roles, gender stereotypes, and occupational aspirations in elementary school children.…”
Section: The Present Researchmentioning
confidence: 99%